2011
DOI: 10.2478/10004-1254-62-2011-2104
|View full text |Cite
|
Sign up to set email alerts
|

High-Risk Biodegradable Waste Processing By Alkaline Hydrolysis

Abstract: High-Risk Biodegradable Waste Processing By Alkaline HydrolysisBiodegradable waste is by definition degraded by other living organisms. Every day, meat industry produces large amounts of a specific type of biodegradable waste called slaughterhouse waste. Traditionally in Europe, this waste is recycled in rendering plants which produce meat and bone meal and fat. However, feeding animals with meat and bone meal has been banned since the outbreaks of bovine spongiform encephalopathy (BSE). In consequence, new sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…This technology is used to destroy animal carcasses, tissues, anatomical parts, blood, body fluids, toxic agents and fixatives (Thacker and Leon 2004;Kalambura et al 2011). For this purpose, it requires an aqueous solution with sodium hydroxide or potassium hydroxide at temperatures around 150-300 ºC to convert all the organic materials present into a sterile solution of small molecules such as proteins, amino acids, carbohydrates and fatty acids salts (Thacker and Leon 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This technology is used to destroy animal carcasses, tissues, anatomical parts, blood, body fluids, toxic agents and fixatives (Thacker and Leon 2004;Kalambura et al 2011). For this purpose, it requires an aqueous solution with sodium hydroxide or potassium hydroxide at temperatures around 150-300 ºC to convert all the organic materials present into a sterile solution of small molecules such as proteins, amino acids, carbohydrates and fatty acids salts (Thacker and Leon 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Education is one of the basic human needs for selfdevelopment. Generally in Indonesia, formal education is divided into several levels, that is basic education which includes elementary and junior high school or equivalent, then secondary education, which includes high school or equivalent, and higher education which consists of programs available at universities such as Bachelor's, Master's or Doctoral degrees [20]. In addition to formal education, waste management knowledge can also be obtained from society's participation in discussion forums or seminars on the theme of waste management [21].…”
Section: Introductionmentioning
confidence: 99%
“…Alkaline hydrolysis is particularly applied in the treatment of contaminated K1 and K2 category tissues [ 11,12]. Earlier studies have shown that alkaline hydrolysis generates a sterile, neutral solution of amino acids, peptides, sugars, and soap [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…This material is a beneficial, highly nutritious solution and an excellent fertilizer. It is also an excellent nutrient source for anaerobic or aerobic sewage treatment plants or biogas plants, often providing micronutrients [11,12,6,15,16].…”
Section: Introductionmentioning
confidence: 99%